Analysis Of Performance Measurement Factors For Achieving Subtainable Development Goals (Sdgs) Targets In The Bandar Lampung City Medium Term Development Plan (Rpjmd) 2021 - 2026 In An Islamic Economic Perspective - Kurniawan, Putra; Sisdianto, Ersi; Hayati , Mardiyah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the key factors, effectiveness of mechanisms, and challenges and opportunities for improving performance measurement of SDGs target achievement in the RPJMD of Bandar Lampung City in 2021-2026. The method used in this study is qualitative with a descriptive analytical research design with SWOT Analysis. Primary data was obtained through interviews with BAPPERIDA Stakeholders of Bandar Lampung City, while secondary data was obtained through literature reviews from journals, books, and other sources that are in line with this study. The results of the study are Analysis shows that the success of Bandar Lampung City in achieving SDGs is highly dependent on data quality, institutional capacity, community participation, and a comprehensive measurement system. However, the city still faces a few challenges such as waste management, pollution, natural disasters, and slums. To overcome these challenges, more integrated and sustainable efforts are needed.